Imported Plasmodium vivax Malaria in the Russian Federation from Western Sub-Saharan Africa - Alla Baranova; Vladimir Sergiev; Lola Morozova; Natalia Turbabina; Evgeny Morozov (Journal of Tropical Medicine)
Background. Imported cases of Plasmodium vivax malaria from western Africa are reported annually in the Russian Federation. Infected native African people moving from western Africa for different purposes (students, businessmen, specialists, etc.) or Russian citizens (tourists, diplomats, businessmen, etc.) incubate the pathogen until reaching their Russian destination. Methods. All imported and other confirmed malaria cases and the associated Plasmodium species recorded over the past twenty years throughout the Russian Federation were inventoried. These data were included in the national register. The data of imported malaria cases were analysed according to the species of Plasmodium, case origin, dates of importation, and patient nationality. Results. A total of 267 P. vivax-infected patients who contracted the disease in western Africa were diagnosed in the Russian Federation from 1984 to 2017. Among them, 3 cases had mixed infections (2 with P. vivax + P. falciparum and 1 P. vivax + P. ovale). Conclusion. Our data reveal an existing risk of contracting P. vivax infections in towns of West sub-Saharan Africa despite the absence of local P. vivax infection records.